Forest stability during the early and late Holocene in the igapó floodplains of the Rio Negro, northwestern Brazil. Issue 1 (January 2018) - Rodríguez-Zorro, Paula A.; Turcq, Bruno; Cordeiro, Renato C.; Moreira, Luciane S.; Costa, Renata L.; McMichael, Crystal H.; Behling, Hermann
Abstract: Located at the northwestern part of the Amazon basin, Rio Negro is the largest black-water river in the world and is one of the poorest studied regions of the Amazon lowlands. In the middle-upper part of the Rio Negro were retrieved sediment cores form Lake Acarabixi, which were analyzed using pollen, spores, charcoal, and geochemistry. The aim of this study was to detect the influences from humans and river dynamics on the vegetation history in the region. Two main periods of vegetation and river dynamics were detected. From 10, 840 to 8240 cal yr BP, the river had a direct influence into the lake. The lake had a regional input of charcoal particles, which reflected the effect of the dry Holocene period in the basin. Furthermore, highland taxa such as Hedyosmum and Myrsine were found at that time along with igapó forest species that are characteristic to tolerate extended flooding like Eschweilera, Macrolobium, Myrtaceae, Swartzia, and Astrocaryum . During the late Holocene (1600 to 650 cal yr BP), more lacustrine phases were observed. There were no drastic changes in vegetation but the presence of pioneer species like Vismia and Cecropia, along with the signal of fires, which pointed to human disturbances.